THE INFLUENCE OF WORD OF MOUTH, NCT DREAM AS A BRAND AMBASSADOR AND BONUS PACK ON BUYING INTEREST IN LEMONILO NOODLE PRODUCTS: (Study on Consumers of Lemonilo Noodle Products in Medan City) - Putri Lubis, Zahwa Nadia; Adlina, Hafiza (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2024)
This research aims to examine the impact of word of mouth, brand ambassadors, and bonus packs on the buying interest of consumers in Medan City who purchase Lemonilo Noodle Products. The study utilizes a quantitative research approach with an associative method. The researchers employed a nonprobability sampling technique, specifically the purposive sampling method. The findings of this study indicate that the word of mouth variable has a significant positive effect on buying interest, as evidenced by the tvalue of 5.074, which is greater than 1.986, and a significance level of 0.000, which is less than 0.05. Similarly, the brand ambassador variable also has a significant positive effect on buying interest, with a tvalue of 2.278, greater than 1.986, and a significance level of 0.001, less than 0.05. Furthermore, the bonus pack variable also demonstrates a significant positive effect on buying interest, with a tvalue of 2.564, greater than 1.986, and a significance level of 0.000, less than 0.05. Additionally, the overall results of this study indicate that all the variables are interconnected, as evidenced by the fvalue of 17.686, greater than 3.09. Hence, this study provides valuable insights into the factors influencing buying interest in Lemonilo Noodle Products.